2020
DOI: 10.1088/1361-6463/ab898f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of barium doping on structural and magnetic properties of bismuth ferrite thin films via spray pyrolysis method

Abstract: Single-phase Bi (1-x) Ba x FeO 3 (0.00 ⩽ x ⩽ 0.20) thin films are successfully deposited on glass substrates by using a spray pyrolysis method. Rietveld analysis of x-ray diffraction patterns confirms that the films are crystallized in a distorted rhombohedral perovskite structure with an R3c space group. No substantial changes in the structure are observed in the samples within the studied doping concentration. The energy dispersive spectroscopy pattern and morphology of the thin films are examined with field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…The present data are not in agreement with the reported data in Ref. [30] that found a decrease in the grain sizes with an increase in Ba due to the oxygen vacancies reduction that appears as an effect of charge compensation mechanism. An increase in grain size has been reported for similar BiFeO 3 system doped with La 3+ [41], NaNbO 3 [42] or even with Ba 3+ [43].…”
Section: Phase Structural and Microstructural Characterizationcontrasting
confidence: 99%
See 3 more Smart Citations
“…The present data are not in agreement with the reported data in Ref. [30] that found a decrease in the grain sizes with an increase in Ba due to the oxygen vacancies reduction that appears as an effect of charge compensation mechanism. An increase in grain size has been reported for similar BiFeO 3 system doped with La 3+ [41], NaNbO 3 [42] or even with Ba 3+ [43].…”
Section: Phase Structural and Microstructural Characterizationcontrasting
confidence: 99%
“…The XRD pattern for Bi 1−x Ba x FeO 3 thin films (where x = 0, 0.02 and 0.05) measured at room temperature is shown in Figure 2. The XRD peaks for x = 0 and 0.05 corresponding to the planes (010), ( 110 [11,21,26,29,30] with the R3m space group identified with ICDS file no. 01-072-2112.…”
Section: Phase Structural and Microstructural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This variation in a values can be related to the ionic radius of Fe 3+ (0.645 Å), Cr 3+ (0.615 Å), and Al 3+ (0.535 Å). Pani et al [13] identified a comparable trend of variation. It is obvious that samples C and A exhibit a lower lattice parameter than that of sample F. According to Bitar et al [48], this variation in the lattice parameter can be attributed to the formation of a secondary phase.…”
Section: Resultsmentioning
confidence: 82%